2023
DOI: 10.7759/cureus.39691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Haematological Parameters and Uric Acid in Diagnosis of Late Onset Neonatal Sepsis

Abstract: Introduction A number of parameters studied in a whole blood count can be helpful in the diagnosis of neonatal sepsis. The platelet/lymphocyte ratio (PLR) is a systemic inflammatory marker in early sepsis and has been used as a diagnostic indicator in cardiovascular events and cancer. Being one of the major antioxidants in human biological fluids, serum uric acid is responsible for neutralising free radicals. The red cell distribution width/platelet ratio (RPR) is a diagnostic marker in adult inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The results showed a positive causal relationship between serum UA levels and sepsis (critical care). In previous studies, Yılmaz Oztorun (51) found that the serum UA levels in patients diagnosed with sepsis (3.77 ± 1.6) were significantly higher compared with the control group (2.83 ± 1.1). The area under the curve for serum UA levels in the diagnosis of confirmed and clinically advanced sepsis ranged from 0.552 to 0.717.…”
Section: Discussionmentioning
confidence: 87%
“…The results showed a positive causal relationship between serum UA levels and sepsis (critical care). In previous studies, Yılmaz Oztorun (51) found that the serum UA levels in patients diagnosed with sepsis (3.77 ± 1.6) were significantly higher compared with the control group (2.83 ± 1.1). The area under the curve for serum UA levels in the diagnosis of confirmed and clinically advanced sepsis ranged from 0.552 to 0.717.…”
Section: Discussionmentioning
confidence: 87%